2021
DOI: 10.5334/jime.628
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Activeness for Potentiating Learning in LMOOCs for Vulnerable Groups

Abstract: In this article the authors present a new concept, activeness, as a dynamic psychological and cognitive state of effective engaged language learning. It is defined in terms of investment, integration and performance, and empowers vulnerable students to exercise control of their learning and progress based on their needs and desired outcomes. It is argued that activeness has a double didactic and linguistic dimension, implemented as a design feature in course materials and activities, and more importantly, prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…The last paper of this cluster (Read & Barcena 2021) considers the potential of LMOOCs to support social inclusion particularly in relation to displaced people such as migrants and Jordan and Goshtasbpour…”
Section: Moocs and Languagesmentioning
confidence: 99%
“…The last paper of this cluster (Read & Barcena 2021) considers the potential of LMOOCs to support social inclusion particularly in relation to displaced people such as migrants and Jordan and Goshtasbpour…”
Section: Moocs and Languagesmentioning
confidence: 99%
“…However, research to date has focused on what might be called a "canon" of LMOOC learning behaviors that includes watching videos, reading class slides, taking quizzes, and participating in discussions in forums (e.g. Duru et al, 2019;Martín-Monje et al, 2018;Read & Bárcena, 2021), but broadly ignores learning check-ins. Learning check-ins denotes a relatively new type of learning behavior in which an LMOOC learner posts/shares part or all of their own learning record or information about their learning-related experience (Chen, Sun, Wu & Song, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, such criticism focuses on low completion rates, lack of social interaction and low learner autonomy (e.g. Friðriksdóttir, 2019; Hsu, 2021a; Jitpaisarnwattana, Reinders & Darasawang, 2021; Read & Bárcena, 2021). Nevertheless, a recent study by Shah (2020) found that, in the wake of the pandemic, language learning had become one of the 10 most-followed MOOC subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Although some post-2017 studies have concluded that LMOOCs are effective (e.g. Meri-Yilan, 2020; Read & Bárcena, 2021; Shalatska, 2018; Wang, An & Wright, 2018; Xue & Dunham, 2021; Zancanaro & Domingues, 2018), others continue to report low completion rates (e.g. Friðriksdóttir, 2019; Hsu, 2021a; Zeng, Zhang, Gao, Xu & Zhang, 2020), lack of intimate and human-like social interaction (Colibaba, Dinu, Gheorghiu & Colibaba, 2018; Hsu, 2021a; Jitpaisarnwattana et al ., 2021; Uchidiuno, Ogan, Yarzebinski & Hammer, 2018), and low levels of learner autonomy (Agonács, Matos, Bartalesi-Graf & O’Steen, 2019).…”
Section: Introductionmentioning
confidence: 99%